Kewarganegaraan dan Tindak Pidana : Pengaruh Status Kewarganegaraan dalam Proses Hukum di Indonesia - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Alifia Syifaurrohmah; Amanah Cantik Lintang Cahyani; Surya Gilang Ramadhan (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
Citizenship plays a crucial role in the legal system and judicial process of any country, including Indonesia. This abstract examines the impact of citizenship status on legal processes in Indonesia, detailing how citizenship affects various aspects of law enforcement, particularly in the context of criminal offenses. In Indonesia, the legal system categorizes individuals as Indonesian citizens (WNI) or foreigners, with each category receiving different legal treatment in criminal cases. In criminal law contexts, the difference in citizenship status can influence several factors, including jurisdiction, legal treatment, and specific rights afforded to both offenders and victims. For Indonesian citizens, legal proceedings are generally conducted under national law, referring to the Indonesian Criminal Code (KUHP) and other relevant statutes. Conversely, foreign nationals involved in criminal acts in Indonesia are subject to special regulations that govern how these cases are handled, including international cooperation and extradition. This study reviews pertinent regulations and judicial practices in Indonesia and explores how citizenship status affects the legal rights of offenders and victims, as well as the procedural aspects of the legal system. The research method used is a qualitative approach, involving case studies and normative analysis. Case studies will include analysis of various criminal cases involving individuals with different citizenship statuses, both Indonesian citizens and non-citizens. Data will be collected through literature reviews, interviews with legal practitioners, and analysis of legal documents and court decisions. The research also addresses the challenges faced in implementing laws related to citizenship status, including issues of human rights, legal protection, and justice. The findings suggest that while Indonesian law provides different treatments based on citizenship, there is an urgent need for harmonization and reform to ensure that legal processes are fair and transparent for all individuals, regardless of their citizenship status. This insight offers guidance on how the Indonesian legal system can be improved to ensure consistent legal protection and justice for all individuals involved in criminal cases.